Focusing of an ultrasonic beam by means of a piezoelectric annular array - WASZCZUK, T.; KUJAWSKA, T.; SOMER, J. C. (Archives of Acoustics, 1983)
The lateral resolution of ultrasonographs for the investigation of the internal structures of the body depends on the diameter of the ultrasonic beam. A decrease in the diameter of the beam can be achieved by the use of multi-element annular ultrasonic probe controlled by the electronic system described in the present paper. This paper also presents a method for the calculation of the distribution of the radiated acoustic field and two experimental methods which permit the measurement of the field distribution, with focusing during transmission only. The analytical results were compared with the experimental results obtained by two measurement methods. This comparison indicates that over the major part of the range there is agreement between the analytical and experimental results. Some differences between them occur mainly at the ends of zone 2 (focal point 60 mm) and in zone 4 (focal point 110 mm).